STRATEGI NAFKAH PEMULUNG DI TEMPAT PEMBUANGAN SAMPAH AKHIR TOISAPU, AMBON (SEBUAH KAJIAN SOSIOLOGIS) - Aty Oni Subair Efrizal Nasution (DIALEKTIKA, 2018)
This study is the result of sociological research on community livelihood strategies of scavengers in Toisapu’s TPA of Ambon. There are two issues that are the focus of research discussions, namely how the scavengers livelihood strategies and how the review of sociology to the the scavengers livelihood strategies in Toisapu’s TPA of Ambon. The method used is descriptive qualitative research. The research subject is scavenger scavenging activity in the study area. The data source consists of expert informants consisting of department heads landscaping and cleanliness of the city of Ambon and Toisapu’s TPA of Ambon managers, and key informants are scavengers who represent the community. The results showed that the livelihood strategies undertaken by the scavengers at Toisapu’s TPA consists of two categories: economic strategy and social strategy. Economic strategies related to the activity as a scavenger to meet the needs of everyday life. Social strategies linked to form a strategy that is not related to the economic aspect or cash directly in the form of a networking, trust and resiprocal